Student Debt Forgiveness and Economic Stability, Social Mobility, and Quality-of-Life Decisions: Results from a Survey Experiment - Jason Jabbari; Stephen Roll; Mathieu Despard; Leah Hamilton (Socius, 2023)
As policymakers grapple with whether or not to forgive student debt, for who, and how much, it is important to explore how student debt forgiveness would relate to intended household decisions and behaviors. We conducted a survey experiment that asked participants with student debt to imagine a scenario in which the federal government forgave a certain amount of student debt. We then had these participants report on how this would affect their decisions and behaviors. A total of 1,053 participants were randomly assigned to one of four conditions that featured different levels of student debt forgiveness. Our results indicate that student debt is strongly influencing intended decisions and behaviors that can have large implications for household economic stability (e.g., emergency savings) and social mobility (e.g., saving for a down payment on a home). These results also demonstrate that the amount of student debt forgiveness matters.